(untitled) - American Automobile Association (New York, NY, 2000)
This classroom-tested program, developed with the American Automobile Association (AAA), reflects the changes surrounding teen driving. Everything your students need to know about driving is included - from graduated driver licensing to zero tolerance laws to information about vehicle maintenance.
Keywords: Automobile driving,Automobile driver education,Giáo dục tài xế,Lái xe